Statistical Metrics for the Temporal Acoustics of Durationally Contrastive Vocalics: A Proposal Tested with Data from Arabic and Japanese - Yahya ALDHOLMI (Archives of Acoustics)
Previous research has utilized the duration ratio and occasionally the duration difference as single-value metrics to measure and compare the temporal acoustics of durationally contrastive vocalics (short vs. long vowels), which allow researchers to reduce two values (short and long) to one, but express a relationship instead of representing the vocalic duration values directly. The duration ratio may even be misleading when comparing two languages or dialects, as it is possible to exhibit a similar ratio but differ in durational acoustics, or vice versa. The current study proposes two alternative statistical metrics: a duration metric and a difference metric. The duration metric is an intermediate (mean-like) value between the duration of the short and long vocalics, and the difference metric is a ± value that can be added to or subtracted from the duration metric to obtain the duration of long or short vocalics. We conduct a production experiment on Arabic and Japanese vocalics and analyze the data using both traditional measures and the proposed metrics. The findings show that the proposed metrics better predict the language from which the vocalic duration values were obtained. Such results suggest that the proposed metrics are better candidates for measuring and comparing the temporal acoustics of vocalics.